Improving the Income of Wood Potatoes (Manihot Utilissima l.) in Medan - Sembiring, Noor (International Journal of Economics and Financial Issues, 2019)
Wood potatoes is the third most important food crop after rice, with the conditions of the study area suitable for developing wood potatoes will be very easy to get benefits, besides those wood potatoes has a fairly low planting and maintenance costs, while the yield or Agricultural development which includes the food crops and horticulture sub-sectors is one of the strategic sub-sectors which economically, ecologically and culture social plays an important role in national development. The purpose of this research is to know the role of Farmers group in increasing wood potatoes farming income. To know the role of farmer group dynamics in increasing wood potatoes farming income. To know the role of Farmers group and the dynamics of farmer groups simultaneously in increasing wood potatoes farming income. The research method used in this study is a quantitative method with a descriptive correlational survey research approach. The dynamics of the farmer group proved to play a positive and significant role in increasing the farming income of Medan Wood potatoes. A dynamics of the farmer group continues to change according to changes in the economic environment and the conditions of the farmers themselves, so that the development of the farmers, in this case, becomes very important because the dynamics of the farmer groups have a big role in increasing farm income. Keywords: income, group dynamic, economics, farmers group JEL Classifications: Q12, Q13, Q18 DOI: https://doi.org/10.32479/ijefi.7434